A fast-response visual indicator film based on polyvinyl alcohol/methylcellulose/black wolfberry anthocyanin for monitoring chicken and shrimp freshness. (December 2022) - Wang, Debao; Wang, Xinxia; Sun, Zhilan; Liu, Fang; Wang, Daoying
Abstract: Natural anthocyanins are considered favorable indicators for new sensing materials because of their wide pH color range. Here, a smart visual indicator film was developed by introducing black wolfberry (BW) anthocyanins to a solid matrix composed of polyvinyl alcohol (PVOH) and methylcellulose (MC). Fourier transform infrared and X-ray showed that the introduction of BW anthocyanins enhanced hydrogen-bond interactions among the polymers and the anthocyanins were well fixed in the polymer matrix. 5 % BW could improve the stability of the PVOH/MC/BW and increase its tensile strength and breakage elongation by 63.2 % and 53.0 %, respectively. Optical observations and freshness monitoring suggested that the film loaded with 5 % BW could respond to acidic and basic vapors within 10 s and as low as 25 ppm NH3 in chicken and shrimp during storage at 4 °C. Therefore, PVOH/MC/BW-5% may potentially be used as a smart sensor to determine freshness in practical applications. Highlights: Visual smart indicator films based on the black wolfberry anthocyanins were prepared. The introduction of 5 % BW improves the stability of PVOH/MC/BW films. The films respond to acidic and basic vapors within 10 s and as low as 25 ppm NH3 . Non-professionals can distinguish the color response of the indicator film. The films indicate sensitively the quality change of chicken and shrimp during storage.